"Chương trình phiên họp chất vấn và trả lời chất vấn (Từ ngày 11-12/11/2024; truyền hình, phát thanh trực tiếp) - Quốc hội (2024)
Chương trình phiên họp chất vấn và trả lời chất vấn (Từ ngày 11-12/11/2024; truyền hình, phát thanh trực tiếp)